Retention of skilled health workers in Africa: the migration–governance–environmental nexus - Limkile Mpofu; Zamokuhle Mbandlwa; Bismarck Shamuzumba; Nigel Manduleli Mpofu; Bhekisisa Dlamini; Simon Sebolao; Tabitha Chinyama; Maleshoane Kalake; Jarrot Mpofu; Dennis Egga (Frontiers in Human Dynamics, 2026)
Background Retaining skilled health workers (SHWs) is a critical challenge for African health systems, where a high disease burden coincides with severe workforce shortages. Traditional Human Resources for Health (HRH) strategies emphasize economic incentives while overlooking the systemic complexities of the migration–governance–environmental nexus. Objective This study examines how governance, political, and environmental factors intersect to shape SHW mobility, evaluating retention strategies in Eswatini, Lesotho, Nigeria, South Africa, Zambia, and Zimbabwe to propose an integrated framework for workforce stabilization. As a perspective paper, the analysis is interpretive rather than statistically inferential, and its claims are scoped accordingly. Methodology Using a comparative, interpretive narrative synthesis, the study integrates 51 retained sources (39 peer-reviewed empirical studies, 12 policy documents) with reflections from 14 African scholars gathered through a rigorous three-round Delphi protocol. Findings Financial incentives offer only temporary relief and are consistently undermined by weak governance, institutional corruption, and environmental stressors. Recurrent droughts and floods act as localized threat multipliers, destabilizing rural livelihoods and degrading clinical workplace safety. The Delphi consensus corroborates and sharpens these findings: panelists identified governance failure, not low pay, as the proximate cause of attrition, and framed climate stress as an amplifier rather than an independent driver, substantiating the Migration–Governance–Environmental Nexus proposed here. Conclusion Sustainable SHW retention requires moving beyond siloed health-sector interventions. Policies must address the health worker's lived reality by embedding climate resilience into facility planning and targeting explicit institutional stakeholders.